2015
DOI: 10.1088/1674-1056/24/3/030504
|View full text |Cite
|
Sign up to set email alerts
|

Robust sliding mode control for fractional-order chaotic economical system with parameter uncertainty and external disturbance

Abstract: This paper presents a modified sliding mode control for fractional-order chaotic economical systems with parameter uncertainty and external disturbance. By constructing the suitable sliding mode surface with fractional-order integral, the effective sliding mode controller is designed to realize the asymptotical stability of fractional-order chaotic economical systems. Comparing with the existing results, the main results in this paper are more practical and rigorous. Simulation results show the effectiveness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Like its integer-order version, [58] system (25) has only one equilibrium 𝐸 0 = {0, 0, 0, 0}. As it has been proved, [58] system (25) When the time-step h = 10 −3 , the coefficients γ = 0.1 and η i = 0.1, i = 1, 2, 3, 4, the numerical results are depicted in Figs. 1(a)-1(c).…”
Section: Examplementioning
confidence: 90%
See 2 more Smart Citations
“…Like its integer-order version, [58] system (25) has only one equilibrium 𝐸 0 = {0, 0, 0, 0}. As it has been proved, [58] system (25) When the time-step h = 10 −3 , the coefficients γ = 0.1 and η i = 0.1, i = 1, 2, 3, 4, the numerical results are depicted in Figs. 1(a)-1(c).…”
Section: Examplementioning
confidence: 90%
“…[9] Intensive studies confirmed theoretically and physically that the chaotic and hyperchaotic behaviors exist the nonlinear fractional-order systems. [3,[8][9][10][11][12][13][14][15] Meanwhile, synchronization of fractional-order chaotic systems also has attracted increasing attention due to its potential applications in secure communication [16,17] and digital cryptography. [18][19][20] A variety of control schemes have been proposed to control and synchronize fractional-order chaos in infinite or finite time, [21,22] such as active control, [23,24] sliding mode control, [25][26][27] adaptive control, [28] passive control, [29] and impulsive control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To counter these nonlinear disturbances, lots of techniques have been proposed, such as adaptive tracking control, [15] model predictive control, [16,17] fuzzy control, [18][19][20][21] sliding mode control. [22][23][24][25][26] H ∞ control is a valid approach to reduce the effect caused by disturbances. As the application of H ∞ control, H ∞ synchronization for a chaotic system is studied in Ref.…”
Section: Introductionmentioning
confidence: 99%